A Study of Computer Related Musculoskeletal and Visual Health Problems among Computer Users and its Association with Desktop Ergonomics in the Gujarat State, A Cross Sectional Study - Nimavat, Nirav; Chhaya, Jatin; Patel, Nilesh; Pandit, Niraj; Upasani, Divija; Vaghela, Jayraj; Vaja, Keyur; Vishnoi, Priyanka; Vora, Kartik (International Journal of Psychosocial Rehabilitation, 2020)
Background: Technological advances, particularly the integration of computers in day-to-day work, lead to musculoskeletal and visual problems. There must be a link between the use of computers and the health-related issues that arise among users. Objectives: To determine the magnitude of musculoskeletal and visual problems, the effect of an increase in time of computer usage on various health issues, and the prevalence of inappropriate ergonomic practices related to computer usage. Results: Around 85% of users were right-handed, and 70% were having education of graduate or above. Among all users, 67% were using desktop and laptop both simultaneously. Around 60% of participants were using computers for more than 8 years. Among all musculoskeletal problems, almost half of the participants have redness of the eye, itching/burning, and irritation of the eye. The majority of the participants had pain/stiffness in their neck and lower back and musculoskeletal-related issues. Conclusions: The neck, lower back, and upper back areas were found to be the most affected areas due to computer usage. Redness, irritation, and itching were common eye-related problems.